ANALYSIS OF COMPANY BANKRUPTCY USING THE GROVER MODEL AND THE SPRINGATE MODEL (Case Study of Food and Beverage Listed on the Indonesia Stock Exchange in 2019-2021) - Siti Nur Fauziah; Mochamad Kohar Mudzakar (SEAN Institute, 2022)
The purpose of this research is to predict bankruptcy with the Grover and Springate models for food and beverage companies listed on the Indonesia Stock Exchange. The study was conducted on 27 companies as samples which were taken based on the purposive sampling technique for the 2019-2021 period. The research method used is explanatory with investigative descriptive. The results of the 2019 Grover Model research, 25 companies are in the healthy category and 2 companies are in the bankrupt category; in 2020, 23 companies are categorized as healthy and 4 companies are categorized as bankrupt; In 2021, 22 companies are categorized as healthy and 5 companies are categorized as bankrupt. The 2019 Springate Model, 20 companies are in the healthy category and 7 companies are in the bankrupt category; in 2020, 18 companies in the healthy category, 1 company in the gray area category and 8 companies in the bankrupt category; In 2021, 15 companies are in the healthy category, 1 company